Korelasi Baldah Thayyibah Dengan Rumusan Maksud Dan Tujuan Muhammadiyah - Dikdik Dahlan Lukman (LPPAIK Universitas Muhammadiyah Bandung, 2021)
This research is intended to understand the relationship between the term baldah thayyibah and the Islamic community which is the ultimate goal of the Muhammadiyah movement. Its main focus includes Muhammadiyah's views on Baldah Thayyibah, the depth of the meaning of the Islamic community, and understanding the country that Muhammadiyah means by Baldah Thayyibah.The research method used is descriptive correlational method, namely raising the problems, bringnig up research questions, collecting relevant data, analyzing data and answering research questions. The analysis was carried out in a correlational manner to answer the relationship between the term baldah thayyibah and the Islamic community. Muhammadiyah views that the Indonesian state is a final national consensus and binds all components of the nation. Therefore, Muhammadiyah focuses on building an Islamic community. Baldah Thayyibah referred to by Muhammadiyah is Indonesia.